Systemic antibodies towards mucosal bacteria in ulcerative colitis and Crohn's disease differentially activate the innate immune response. Issue 1 (18th December 2003) - Furrie, E; Macfarlane, S; Cummings, J H; Macfarlane, G T
Abstract : Background and aims: The mucosa in ulcerative colitis (UC) is replete with antibody producing plasma B cells and polymorphonuclear leucocytes (PMN). This combination of effector cells requires a crosslinking antigen to evoke an antibody driven PMN inflammatory response via their Fc receptors. The stimulus for activation is thought to be commensal bacteria colonising the gut mucosa. The aim of this investigation was to compare the principal culturable bacterial populations on the rectal mucosa of UC patients, and to determine whether specific antibodies towards these bacteria can activate infiltrating PMN through opsonisation. This would provide an explanation for this chronic inflammatory condition. Methods: Bacteria colonising rectal tissue were characterised using chemotaxonomic techniques. Systemic antibody responses were measured against total antigens and surface antigens of these organisms in UC and Crohn's disease (CD) patients, together with healthy controls. Antibody enhancement of the respiratory burst in PMN was also investigated, against a range of mucosal isolates. Results: Distinct differences were observed in some bacterial populations in UC biopsies, which were generally reflected in antibody responses towards these organisms. UC patients had higher IgG responses to surface antigens, primarily IgG1, whereas the response in CD was mainly IgG2. Antibodies from UC patients greatly enhanced the respiratory burst in PMN, in response to individual bacterial species. Conclusions: Changes in mucosal bacteria, and a switch from internal to surface antigen/antibody reactivity of a predominantly IgG1 type, leads to greater opsonisation of the respiratory burst in PMN, providing a mechanism for maintaining the inflammatory state in UC.